Contemporary Pentecostal Christianity : Interpretations from an African Context - Asamoah-Gyadu, J. Kwabena (Johnson Kwabena) (Book collections on Project MUSE., 2013)
Pentecostalism is the fastest-growing stream of Christianity in the world. The real evidence for the significance of Pentecostalism lies in the actual churches built and the number of people attracted. In Africa, Pentecostalism has virtually become the representative face of Christianity, with even historic mission denominations "pentecostalizing" their otherwise formal liturgical structures to survive. This work interprets key theological and missiological themes in African Pentecostalism by using material from the lived experiences of the movement itself.